High‐resolution analysis of individual spike peptide‐specific CD4+ T‐cell responses in vaccine recipients and COVID‐19 patients. Issue 8 (9th August 2022) - Karsten, Hendrik; Cords, Leon; Westphal, Tim; Knapp, Maximilian; Brehm, Thomas Theo; Hermanussen, Lennart; Omansen, Till Frederik; Schmiedel, Stefan; Woost, Robin; Ditt, Vanessa; Peine, Sven; Lütgehetmann, Marc; et al.
Abstract: Objectives: Potential differences in the breadth, distribution and magnitude of CD4 + T‐cell responses directed against the SARS‐CoV‐2 spike glycoprotein between vaccinees, COVID‐19 patients and subjects who experienced both ways of immunisation have not been comprehensively compared on a peptide level. Methods: Following virus‐specific in vitro cultivation, we determined the T‐cell responses directed against 253 individual overlapping 15‐mer peptides covering the entire SARS‐CoV‐2 spike glycoprotein using IFN‐γ ELISpot and intracellular cytokine staining. In vitro HLA binding was determined for selected peptides. Results: We mapped 955 single peptide‐specific CD4 + T‐cell responses in a cohort of COVID‐19 patients ( n  = 8), uninfected vaccinees ( n  = 16) and individuals who experienced both infection and vaccination ( n  = 11). Patients and vaccinees (two‐time and three‐time vaccinees alike) had a comparable number of CD4 + T‐cell responses (median 26 vs. 29, P  = 0.7289). Most of these specificities were conserved in B.1.1.529 and the BA.4 and BA.5 sublineages. The highest magnitude of these in vitro IFN‐γ CD4 + T‐cell responses was observed in COVID‐19 patients (median 0.35%), and three‐time vaccinees showed a higher magnitude than two‐time vaccinees (median 0.091% vs. 0.175%, P  < 0.0001). Twelve peptide specificities were each detected in at least 40% of subjects. In vitro HLA binding showed promiscuous presentation by DRB1 molecules for several peptides. Conclusion: Both SARS‐CoV‐2 infection and vaccination prime broadly directed T‐cell responses directed against the SARS‐CoV‐2 spike glycoprotein. This comprehensive high‐resolution analysis of spike peptide specificities will be a useful resource for further investigation of spike‐specific T‐cell responses. Abstract : Individual CD4 + and CD8 + T‐cell responses directed against a total of 253 overlapping 15‐mer spike‐specific peptides were mapped in a cohort of COVID‐19 patients ( n  = 8), uninfected vaccinees ( n  = 16) and individuals who experienced both infection and vaccination ( n  = 11). We found that patients and vaccinees (two‐time and three‐time vaccinees alike) had a comparable number of CD4 + T‐cell responses (median 26 vs. 29, P  = 0.7289) but differential magnitudes of these in vitro responses (median 0.35% vs. 0.12% IFN‐γ + of CD4 + T cells, P  < 0.0001). Most of the recognized specificities were conserved in the B.1.1.529 (omicron) Variant of Concern (VoC), and its sublineages and several peptides showed promiscuous presentation by DRB1 molecules in in vitro HLA‐binding assays.